Pemurnian Selulosa-α Hasil Hidrolisis Pelepah Sawit Menggunakan Enzim Xylanase Dengan Variasi pH Dan Sumber Enzim Xylanase - Sari D. P; Padil Padil; Yelmida Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Midrib palm is one of the waste that produced from palm farming which contain alpha cellulose about 35%. The component of alpha cellulose could be used as a raw material for nitrocellulose if it is has more than 92% of purity. So to increase the purity of alpha cellulose, midrib palm has to be treated by purifying step. In this time, chemical still be choices to be material for purify alpha cellulose, while as we know that chemical has a bad impact for our envirotment. So it is important to search another purifying agent and it is xylanase. Xylanase is one of enzyme that has an ability to break up the link between xylose in xylan. So the purpose of this research are to use xylanase as another purifying agent, to know what is the best pH for this purifying process and to compare the result between two xylanases that produced from different fungi. Before start the purifying step, midrib have to through extraction step to remove all extractive and continue with hydrolisis step by using extraction liquid of palm empty bunch ash. Then after that purifying step can be done at 600C for 1,5 hours by making some differences at pH (4,5 and 6). The highest purity of alpha cellulose was reached at pH 6 by using xylanase from Aspergillus niger about 97,55%. So the conclucion of this research are, the best pH for purifying process by using xylanase is 6 and the best xylanase is the one which produce from Aspergillus niger. Beside that, the use of xylanase which is comes from the same species will be not affected much to the purifying result.Keyword : hydrolisis, midrib palm, xylanase enzyme